Kecerdasan spiritual dalam konsep pendidikan lukman - Mujahidah (ARKA INSTITUTE, 2022)
Lukman in the Quran, Surah Lukman verses 12–19, highlights aspects of spiritual intelligence. Islamic education as reflected in Lukman Hakim's teachings emphasizes the importance of spiritual intelligence in everyday life, which is reflected through values such as amar ma'ruf nahi munkar, gratitude, and patience. This research aims to explore the concept of education. This research identifies that individuals who have spiritual intelligence tend to care more about others and are better able to overcome life's challenges. The method used is library research because the data studied is in the form of manuscripts, books, or magazines sourced from the literature. The technique used to obtain data for this article is library research, namely library research or pure research. Descriptive analytics and interpretation are the data analysis techniques used. The results of this research show that the concept of spiritual intelligence in Surah Lukman verses 12–19 has important aspects, including spiritual, mental, and social dimensions. These dimensions include values such as gratitude, obedience to Allah, religious practices such as prayer, and good social behavior towards others and family. These findings underscore the urgency of building spiritual intelligence in education in an effort to form better individuals in society.